Intra oral sprays -An overview (International Journal of Pharmacy and Life Sciences, 2011)
Over the last three decades, intraoral dosage forms have been evolving as an acceptable and in some cases as the preferred, alternative to conventional tablets and capsules. Among them, Oral sprays are the fastest, most effective and comfortable way to take medicines, nutrients, minerals and vitamins. They have been acquiring important position in the market by overcoming previously encountered administration problems and contributing to extension of patent life. Oral sprays have the unique property of rapidly releasing the drug in the oral cavity, thus obviating the requirement of water during administration. Therefore, these dosage forms have lured the market for a certain section of the patient population which includes dysphagic, bed ridden, and psychic, geriatric patients. This article focuses on the transmucosal view , spray formulation aspects , advances made so far in the field oral sprays and patented technologies.